Advances in three-dimensional coronary imaging and computational fluid dynamics: is virtual fractional flow reserve more than just a pretty picture?. (August 2015) - Poon, Eric K.W.; Hayat, Umair; Thondapu, Vikas; Ooi, Andrew S.H.; Asrar Ul Haq, Muhammad; Moore, Stephen; Foin, Nicolas; Tu, Shengxian; Chin, Cheng; Monty, Jason P.; Marusic, Ivan; Barlis, Peter
Abstract : Percutaneous coronary intervention (PCI) has shown a high success rate in the treatment of coronary artery disease. The decision to perform PCI often relies on the cardiologist's visual interpretation of coronary lesions during angiography. This has inherent limitations, particularly due to the low resolution and two-dimensional nature of angiography. State-of-the-art modalities such as three-dimensional quantitative coronary angiography, optical coherence tomography and invasive fractional flow reserve (FFR) may improve clinicians' understanding of both the anatomical and physiological importance of coronary lesions. While invasive FFR is the gold standard technique for assessment of the haemodynamic significance of coronary lesions, recent studies have explored a surrogate for FFR derived solely from three-dimensional reconstruction of the invasive angiogram, and therefore eliminating need for a pressure wire. Utilizing advanced computational fluid dynamics research, this virtual fractional flow reserve (vFFR) has demonstrated reasonable correlation with invasive measurements and remains an intense area of ongoing study. However, at present, several limitations and computational fluid dynamic assumptions may preclude vFFR from widespread clinical use. This review demonstrates the tight integration of advanced three-dimensional imaging techniques and vFFR in assessing coronary artery disease, reviews the advantages and disadvantages of such techniques and attempts to provide a glimpse of how such advances may benefit future clinical decision-making during PCI.